2012
DOI: 10.1186/preaccept-1659425760561038
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of cryotherapy versus salicylic acid for the treatment of plantar warts: economic evaluation alongside a randomised controlled trial (EVerT trial)

Abstract: Background: Plantar warts (verrucae) are extremely common. Although many will spontaneously disappear without treatment, treatment may be sought for a variety of reasons such as discomfort. There are a number of different treatments for cutaneous warts, with salicylic acid and cryotherapy using liquid nitrogen being two of the most common forms of treatment. To date, no full economic evaluation of either salicylic acid or cryotherapy has been conducted based on the use of primary data in a pragmatic setting. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Another method of physical destruction commonly used is cryotherapy. Despite not leaving scars, studies have shown that in some cases, cryotherapy is no more effective than the application of topical Salicylic Acid and is more expensive . The HPV virus has also been found to respond more to treatment with heat (hyperthermia) compared to cryotherapy – suggesting that laser ablation kills the virus more effectively .…”
Section: Discussionmentioning
confidence: 99%
“…Another method of physical destruction commonly used is cryotherapy. Despite not leaving scars, studies have shown that in some cases, cryotherapy is no more effective than the application of topical Salicylic Acid and is more expensive . The HPV virus has also been found to respond more to treatment with heat (hyperthermia) compared to cryotherapy – suggesting that laser ablation kills the virus more effectively .…”
Section: Discussionmentioning
confidence: 99%
“…Topical agents such as salicylic acid and cantharidin may have beneficial effect on verruca vulgaris and verruca plantaris [21][22][23]. But these agents should not be used by patients themselves theoretically.…”
Section: Discussionmentioning
confidence: 99%
“…Another commonly used method of physical destruction is cryotherapy. Despite not leaving scars, cryotherapy is not more effective than topical salicylic acid in some cases [21][22][23]. Besides, these aggressive treatments often cause intolerable pain, hyperpigmentation, hypopigmentation, or occasionally allergic contact dermatitis [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…As no controlled double‐blind clinical trials exist, there is no consensus about the most suitable concentration to use (generally 1–3%), its application scheme (1–2 times daily, with or without occlusion), or the optimal duration of treatment. Accordingly, further studies are required to define these factors .…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of PW has involved several different modes, including ablative therapy and other options that modify the immune response . Cidofovir is a potent antiviral agent that inhibits the activity of DNA polymerase and that has been approved for the intravenous treatment of retinitis due to cytomegalovirus in immunosuppressed patients .…”
Section: Introductionmentioning
confidence: 99%